PENGARUH CITRA MEREK, NILAI, KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (Studi: Pada Pelanggan Pasta Gigi Pepsodent di Kelurahan Sukolilo â Pati) - RifÃ¢Â€Â™an, 08.05.51.0052 Mohamad; Budi Setyawan, Mulyo (Students Journal of Economic and Management, 2012)
Sukolilo-Starch. Determination of the samples was done by using "purposive sampling" which is a technique of determining if the information for the data samples taken from specific targets, bytaking a sample with specific criteria to be selected into the sample and the number of samples taken as many as 100 people .Data collected were analyzed using Analysis factor to test the validity of the question items The study entitled "Effect of Brand Image, Value, Customer Satisfaction Of Customer Loyalty" is done in order to analyze customer loyalty Pepsodent toothpaste products in the Village Sukolilo-Pati. The population in this study is the customers who use Pepsodent toothpaste products in the Village, alpha cronbach formula to test the reliability, regression analysis to test each variable partially free with koefesiensi detrminasi tested. The results showed that the brand image but not significant positive effect on customer loyalty. Has positive and significant value to the customer loyaliyas. Customer satisfaction but not significant positive effect on customer loyalty.Keywords: brand image, value, Customer Satisfaction and Customer Loyalty.